A preparation method, material and application of phosphorus-doped cobalt aluminum / carbon-based composite material

Through the preparation method of phosphorus-doped cobalt aluminum/carbon matrix composite materials, the existing thermal wave absorption materials have been solved, and the high thermal conductivity and excellent electromagnetic wave absorption performance are achieved, which is suitable for multifunctional integration and green environmental protection requirements.

CN118908294BActive Publication Date: 2025-03-28HEFEI UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410920177.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-10
Publication Date
2025-03-28
Estimated Expiration
2044-07-10

AI Technical Summary

Technical Problem

While existing thermal wave absorbing materials have high thermal conductivity and excellent electromagnetic wave absorption performance, the process is complex and difficult to meet the requirements of multifunctional integration and green environmental protection.

Method used

The preparation method of phosphorus-doped cobalt aluminum/carbon-based composite material is adopted to prepare a regular morphological modified cobalt aluminum dihydroxide by hydrothermal and modification treatment, and carbonization is carried out under a high temperature inert atmosphere to form a composite material with high thermal conductivity and wave absorption properties.

Benefits of technology

It achieves high thermal conductivity (0.731W/(m·K) and excellent electromagnetic wave absorption performance (reflection loss performance up to -59dB, effective absorption bandwidth of 4.6GHz). At the same time, the process is simple, the raw materials are green and environmentally friendly, and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118908294B_ABST
    Figure CN118908294B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermal conductive wave absorbing materials, and relates to a preparation method, material and application of a phosphorus-doped cobalt aluminum / carbon-based composite material, comprising: using cobalt chloride hexahydrate, aluminum chloride hexahydrate, urea and deionized water for hydrothermal reaction to obtain cobalt aluminum double hydroxide; using ethanol and polyvinyl pyrrolidone to modify the obtained cobalt aluminum double hydroxide to obtain modified cobalt aluminum double hydroxide; using sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water and gelatin for a first water bath reaction to obtain a third precursor solution; using formaldehyde, tannic acid and the third precursor solution for a second water bath reaction and freezing and drying, and carbonizing the obtained sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite in a nitrogen atmosphere to obtain a phosphorus-doped cobalt aluminum / carbon-based composite material. The invention can prepare a thermal conductive wave absorbing material with a small filling amount, a large wave absorbing strength and a high thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of heat-conducting and wave-absorbing materials, and in particular to a preparation method, material and application of a phosphorus-doped cobalt aluminum / carbon-based composite material. Background Art

[0002] The rapid development of miniaturization, integration and high performance of electronic devices has led to serious problems such as electromagnetic interference and heat accumulation. Electromagnetic interference not only affects the operation of instruments and equipment, causes information leakage, but also harms human health. In addition, excessive heat from the equipment cannot be dissipated in time, which may lead to aging and failure of internal components. In the military fields such as aerospace, weapons and equipment, and aircraft, there are demands for radar stealth and rapid heat dissipation, which puts higher requirements on electromagnetic stealth and thermal management. In order to solve these problems, the research and development of thermal conductive and wave-absorbing materials with excellent performance has attracted continuous attention.

[0003] Carbon aerogel has broad development potential in the field of thermal conductive and wave absorbing materials due to its high specific surface area, low density and unique three-dimensional network structure. However, carbon aerogel has the problem of single loss mechanism and low thermal conductivity. At present, the strategy of combining magnetic metal and carbon aerogel is mainly used to improve it. However, there are few studies on the multifunctional properties of magnetic metal / carbon aerogel for thermal conductive and wave absorbing. The Chinese patent with publication number CN115612461A discloses a three-dimensional high thermal conductive attapulgite / graphene oxide aerogel composite phase change material and a preparation method. The attapulgite / graphene oxide aerogel composite phase change material is obtained by mixing the acidified and amino attapulgite with the graphene oxide suspension through hydrothermal, freeze drying and vacuum impregnation. The attapulgite / graphene oxide aerogel prepared by this method has a thermal conductivity of 1.164W / (m·K), but the preparation process is time-consuming and complicated, which is not conducive to large-scale production. A Chinese patent with publication number CN117263172A discloses a method for preparing a structurally enhanced magnetic graphene aerogel absorbing material. Iron oxide nanorods are mixed with a graphene oxide solution prepared by the Hummers method and hydrazine hydrate, and then freeze-dried and heat-treated to obtain a magnetic graphene aerogel. The magnetic graphene aerogel prepared by this method exhibits an absorbing performance of -52.77 dB. However, the aerogel material obtained by this method has a single function and cannot simultaneously have thermal conductivity and wave absorption properties, making it difficult to meet multifunctional integrated application scenarios. Some of the raw materials used are difficult to meet the increasingly high green environmental protection requirements. The high-purity preparation and processing costs of graphite are high. The preparation of graphite aerogel often requires high temperature, complex chemical reactions and special equipment, which increases the process complexity and energy consumption.

[0004] Therefore, how to provide a material that has both high thermal conductivity and excellent electromagnetic wave absorption performance with simple process has become an urgent problem to be solved. Summary of the invention

[0005] In view of this, in order to overcome the deficiencies of the prior art, the present invention provides a method for preparing a phosphorus-doped cobalt aluminum / carbon-based composite material, a material and an application thereof.

[0006] According to one aspect of the present invention, the present invention provides a method for preparing a phosphorus-doped cobalt aluminum / carbon-based composite material, the method comprising the following steps:

[0007] Step 1: Preparation of modified cobalt aluminum double hydroxide

[0008] A first precursor solution is prepared by using cobalt chloride hexahydrate, aluminum chloride hexahydrate, urea and deionized water according to a ratio, the prepared first precursor solution is subjected to a hydrothermal reaction, and the hydrothermal reaction product is washed and dried to obtain cobalt aluminum double hydroxide;

[0009] The prepared cobalt aluminum double hydroxide is modified by using ethanol and polyvinyl pyrrolidone according to a ratio, and the modified product is washed and dried to obtain modified cobalt aluminum double hydroxide;

[0010] Step 2: Preparation of sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite

[0011] Sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water, gelatin, formaldehyde and tannic acid are prepared according to the proportion;

[0012] Sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water and gelatin are mixed according to a ratio to prepare a second precursor solution, and the prepared second precursor solution is subjected to a first water bath reaction to obtain a third precursor solution;

[0013] Adding formaldehyde and tannic acid to the third precursor solution according to a ratio to prepare a fourth precursor solution, subjecting the prepared fourth precursor solution to a second water bath reaction, and freezing and drying the second water bath reaction product to obtain a sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite;

[0014] Step 3: Preparation of phosphorus-doped cobalt aluminum / carbon-based composite materials

[0015] The sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite is carbonized in a nitrogen atmosphere to prepare a phosphorus-doped cobalt aluminum / carbon-based composite material.

[0016] Preferably, in the method for preparing a phosphorus-doped cobalt aluminum / carbon-based composite material of the present invention, in step one, a first precursor solution is prepared by using cobalt chloride hexahydrate, aluminum chloride hexahydrate, urea and deionized water in a ratio, comprising: adding cobalt chloride hexahydrate, aluminum chloride hexahydrate and urea to deionized water in a ratio, and ultrasonically treating for 5-10 minutes to obtain a first precursor solution having a cobalt chloride hexahydrate concentration of 0.01 mol / L, an aluminum chloride hexahydrate concentration of 0.09 mol / L, and a urea concentration of 0.035 mol / L.

[0017] Preferably, in the method for preparing the phosphorus-doped cobalt aluminum / carbon-based composite material of the present invention, in step one, a hydrothermal reaction is performed on the prepared first precursor solution, and the hydrothermal reaction product is washed and dried, including: hydrothermally reacting the first precursor solution at 100°C for 24 hours, centrifugally washing the hydrothermal reaction product 2-3 times with anhydrous ethanol and deionized water respectively, at a centrifugal speed of 5000 r / min, the time for each centrifugal washing is 1 min, and the product after centrifugal washing is dried at 60°C for 24 hours.

[0018] Preferably, the method for preparing the phosphorus-doped cobalt aluminum / carbon-based composite material of the present invention comprises, in step 1, modifying the prepared cobalt aluminum double hydroxide with ethanol and polyvinyl pyrrolidone according to a ratio, washing and drying the modified product, comprising:

[0019] Dissolving cobalt aluminum double hydroxide in anhydrous ethanol according to a ratio and adding polyvinyl pyrrolidone to prepare a modified solution with a concentration of 3.3 g / L of cobalt aluminum double hydroxide and a concentration of 0.03 mol / L of polyvinyl pyrrolidone;

[0020] The prepared modified solution was stirred at room temperature at a stirring speed of 300-500 r / min for 8-15 h, and the stirred product was centrifugally washed 2-3 times with anhydrous ethanol and deionized water respectively, the centrifugal speed was 5000 r / min, and the time of each centrifugal washing was 1 min. The product after centrifugal washing was dried at 60°C for 12-24 h.

[0021] Preferably, in the method for preparing the phosphorus-doped cobalt aluminum / carbon-based composite material of the present invention, in step 2, sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water, gelatin, formaldehyde and tannic acid are prepared according to the ratio, including: 0.2-0.8 mg of sodium hypophosphite, 4 mg of modified cobalt aluminum double hydroxide material, 0.06-0.1 g of gelatin, 2 μL of formaldehyde and 0.002 mg of tannic acid per 1 ml of deionized water.

[0022] Preferably, in the method for preparing a phosphorus-doped cobalt aluminum / carbon-based composite material of the present invention, in step 2, sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water and gelatin are prepared in a ratio to prepare a second precursor solution, and the prepared second precursor solution is subjected to a first water bath reaction to obtain a third precursor solution, comprising: dissolving sodium hypophosphite and modified cobalt aluminum double hydroxide in deionized water in a ratio, ultrasonically treating for 5-10 minutes, adding gelatin and standing at room temperature for 30-50 minutes to obtain a second precursor solution, and subjecting the second precursor solution to a first water bath reaction at 50°C for 30 minutes to obtain a third precursor solution.

[0023] Preferably, in the method for preparing the phosphorus-doped cobalt aluminum / carbon-based composite material of the present invention, in step two, the prepared fourth precursor solution is subjected to a second water bath reaction, and the product of the second water bath reaction is frozen and dried, including: subjecting the fourth precursor solution to a second water bath reaction at 50°C for 20 minutes, and freeze-drying the product of the second water bath reaction at -80°C for 24-48 hours.

[0024] Preferably, in the method for preparing the phosphorus-doped cobalt aluminum / carbon-based composite material of the present invention, in step three, the sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite is carbonized in a nitrogen atmosphere, including: placing the sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite in a nitrogen atmosphere, heating the temperature to 600-800°C at a heating rate of 2°C / min, keeping the temperature for 2h, cooling the temperature to 500°C at 5°C / min, and naturally cooling the temperature to room temperature.

[0025] According to another aspect of the present invention, the present invention provides a phosphorus-doped cobalt aluminum / carbon-based composite material, which is prepared according to the above method.

[0026] According to another aspect of the present invention, the present invention provides an application of a phosphorus-doped cobalt aluminum / carbon-based composite material as a thermal conductive and wave absorbing material.

[0027] The phosphorus-doped cobalt aluminum / carbon-based composite material preparation method, material and application of the present invention have the following beneficial effects:

[0028] 1. Through hydrothermal and modification treatment, modified cobalt aluminum double hydroxide with regular morphology, uniform size and better dispersibility is prepared. The surface of modified cobalt aluminum double hydroxide is rich in polar groups and can form a good interface with aerogel. The magnetic component cobalt can provide strong magnetic loss, and the aluminum component plays a dual role. On the one hand, it can adjust the impedance matching and improve the wave absorption characteristics of the structure. On the other hand, it can increase the transmission free path of phonons and improve thermal conductivity. The synergistic effect of thermal conductivity and wave absorption of phosphorus-doped cobalt aluminum / carbon-based materials is significantly enhanced;

[0029] 2. During the water bath and freeze-drying preparation process, the controlled addition of formaldehyde and tannic acid promoted the cross-linking of gelatin molecular chains, thereby obtaining a highly stable sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel high porosity composite. The aerogel has a rich pore structure and a large specific surface area. While reducing the density, it can also make electromagnetic waves reflect and absorb multiple times;

[0030] 3. Phosphorus-doped cobalt aluminum / carbon-based composites were prepared by phosphorus doping in a high-temperature inert atmosphere, which significantly increased the electron concentration of the system and achieved efficient electron transmission in the three-dimensional interconnected structure of the material, thereby enhancing the ability of electron heat transfer and electrical conductivity loss, while also improving the crystallinity of the material and the degree of graphitization of carbon;

[0031] 4. The phosphorus-doped cobalt aluminum / carbon-based composite material prepared by the present invention has a reflection loss performance of -59dB, an effective wave absorption bandwidth of 4.6GHz, and a thermal conductivity of 0.731W / (m·K). It has a small filling amount, a large wave absorption intensity, and a high thermal conductivity, showing excellent thermal conductive wave absorption performance, which is conducive to the preparation of a new type of "thin, light, wide, and strong" thermal conductive wave absorbing material.

[0032] 5. The raw materials of the method of the present invention are green and environmentally friendly, the cost is controllable, the repeatability is good, the preparation cycle is short and the energy consumption is low, no special equipment is required, and it is suitable for large-scale production and application. The prepared phosphorus-doped cobalt aluminum / carbon-based composite thermal conductive and absorbing material is more competitive in multifunctional integrated application scenarios such as electronic packaging, medical equipment, antenna materials, and 5G base stations. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is the laser Raman spectrum of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 1 of the present invention;

[0035] Figure 2 This is the laser Raman spectrum of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 2 of the present invention;

[0036] Figure 3 This is the laser Raman spectrum of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 3 of the present invention;

[0037] Figure 4 This is the laser Raman spectrum of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 4 of the present invention;

[0038] Figure 5 This is the laser Raman spectrum of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 5 of the present invention;

[0039] Figure 6 This is the laser Raman spectrum of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 6 of the present invention;

[0040] Figure 7 This is a scanning electron microscope image of the sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite prepared in Example 5 of the present invention;

[0041] Figure 8 This is a scanning electron microscope image of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 5 of the present invention;

[0042] Fig. 9 This is an element distribution diagram of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 5 of the present invention;

[0043] Fig.10 This is a reflection loss curve of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 2 of the present invention;

[0044] Fig.11 This is a reflection loss curve of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0045] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0046] It should be noted that the following embodiments and features in the embodiments may be combined with each other in the absence of conflict; and, based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making any creative work are within the scope of protection of the present disclosure.

[0047] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.

[0048] Example 1

[0049] A method for preparing a phosphorus-doped cobalt aluminum / carbon-based composite material:

[0050] Step 1: Preparation of modified cobalt aluminum double hydroxide

[0051] Cobalt chloride hexahydrate, aluminum chloride hexahydrate and urea are added to deionized water according to a ratio, and ultrasonically treated for 5 minutes to obtain a first precursor solution having a concentration of 0.01 mol / L of cobalt chloride hexahydrate, 0.09 mol / L of aluminum chloride hexahydrate and 0.035 mol / L of urea;

[0052] The first precursor solution was subjected to a hydrothermal reaction at 100° C. for 24 hours, and the hydrothermal reaction product was centrifugally washed twice with anhydrous ethanol and deionized water respectively, the centrifugal speed was 5000 r / min, and the time of each centrifugal washing was 1 minute, and the product after centrifugal washing was dried at 60° C. for 24 hours to obtain cobalt aluminum double hydroxide;

[0053] Dissolving cobalt aluminum double hydroxide in anhydrous ethanol according to a ratio and adding polyvinyl pyrrolidone to prepare a modified solution with a concentration of 3.3 g / L of cobalt aluminum double hydroxide and a concentration of 0.03 mol / L of polyvinyl pyrrolidone;

[0054] The prepared modified solution was stirred at room temperature at a stirring speed of 300 r / min for 8 hours, and the stirred product was centrifugally washed twice with anhydrous ethanol and deionized water respectively, the centrifugal speed was 5000 r / min, and the time of each centrifugal washing was 1 minute. The product after centrifugal washing was dried at 60° C. for 12 hours to obtain modified cobalt aluminum double hydroxide;

[0055] Step 2: Preparation of sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite

[0056] Sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water, gelatin, formaldehyde and tannic acid are prepared according to the ratio. Specifically, 0.2 mg of sodium hypophosphite, 4 mg of modified cobalt aluminum double hydroxide material, 0.06 g of gelatin, 2 μL of formaldehyde and 0.002 mg of tannic acid are prepared for every 1 ml of deionized water;

[0057] Sodium hypophosphite and modified cobalt aluminum double hydroxide were dissolved in deionized water according to the ratio, and gelatin was added after ultrasonic treatment for 5 minutes and allowed to stand at room temperature for 30 minutes to obtain a second precursor solution, and the second precursor solution was reacted in a first water bath at 50° C. for 30 minutes to obtain a third precursor solution;

[0058] Adding formaldehyde and tannic acid to a third precursor solution according to a ratio to prepare a fourth precursor solution, performing a second water bath reaction on the prepared fourth precursor solution, and freezing and drying the product of the second water bath reaction, including: performing a second water bath reaction on the fourth precursor solution at 50° C. for 20 minutes, and freeze-drying the product of the second water bath reaction at -80° C. for 24 hours to obtain a sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite;

[0059] Step 3: Preparation of phosphorus-doped cobalt aluminum / carbon-based composite materials

[0060] The sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite was placed in a nitrogen atmosphere, heated to 600°C at a heating rate of 2°C / min, kept at this temperature for 2h, cooled to 500°C at a rate of 5°C / min, and naturally cooled to room temperature to obtain a phosphorus-doped cobalt aluminum / carbon-based composite material.

[0061] Example 2

[0062] A method for preparing a phosphorus-doped cobalt aluminum / carbon-based composite material:

[0063] Step 1: Preparation of modified cobalt aluminum double hydroxide

[0064] Cobalt chloride hexahydrate, aluminum chloride hexahydrate and urea are added to deionized water according to a ratio, and ultrasonic treatment is performed for 8 minutes to obtain a first precursor solution having a concentration of 0.01 mol / L of cobalt chloride hexahydrate, 0.09 mol / L of aluminum chloride hexahydrate and 0.035 mol / L of urea;

[0065] The first precursor solution was subjected to a hydrothermal reaction at 100° C. for 24 hours, and the hydrothermal reaction product was centrifugally washed three times with anhydrous ethanol and deionized water, respectively, at a centrifugal speed of 5000 r / min, and the time of each centrifugal washing was 1 minute. The product after centrifugal washing was dried at 60° C. for 24 hours to obtain cobalt aluminum double hydroxide;

[0066] Dissolving cobalt aluminum double hydroxide in anhydrous ethanol according to a ratio and adding polyvinyl pyrrolidone to prepare a modified solution with a concentration of 3.3 g / L of cobalt aluminum double hydroxide and a concentration of 0.03 mol / L of polyvinyl pyrrolidone;

[0067] The prepared modified solution was stirred at room temperature at a stirring speed of 400 r / min for 10 h, and the stirred product was centrifugally washed three times with anhydrous ethanol and deionized water respectively, the centrifugal speed was 5000 r / min, and the time of each centrifugal washing was 1 min. The product after centrifugal washing was dried at 60° C. for 18 h to obtain modified cobalt aluminum double hydroxide;

[0068] Step 2: Preparation of sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite

[0069] Sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water, gelatin, formaldehyde and tannic acid are prepared according to the ratio. Specifically, 0.4 mg of sodium hypophosphite, 4 mg of modified cobalt aluminum double hydroxide material, 0.07 g of gelatin, 2 μL of formaldehyde and 0.002 mg of tannic acid are prepared for every 1 ml of deionized water;

[0070] Sodium hypophosphite and modified cobalt aluminum double hydroxide were dissolved in deionized water according to the ratio, and gelatin was added after ultrasonic treatment for 7 minutes and allowed to stand at room temperature for 30 minutes to obtain a second precursor solution, and the second precursor solution was reacted in a first water bath at 50° C. for 30 minutes to obtain a third precursor solution;

[0071] Adding formaldehyde and tannic acid to a third precursor solution according to a ratio to prepare a fourth precursor solution, performing a second water bath reaction on the prepared fourth precursor solution, and freezing and drying the second water bath reaction product, including: performing a second water bath reaction on the fourth precursor solution at a temperature of 50° C. for 20 minutes, freeze-drying the second water bath reaction product at a temperature of -80° C. for 48 hours, and preparing a sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite;

[0072] Step 3: Preparation of phosphorus-doped cobalt aluminum / carbon-based composite materials

[0073] The sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite was placed in a nitrogen atmosphere, heated to 700°C at a heating rate of 2°C / min, kept at this temperature for 2h, cooled to 500°C at a rate of 5°C / min, and then naturally cooled to room temperature to obtain a phosphorus-doped cobalt aluminum / carbon-based composite material.

[0074] Example 3

[0075] A method for preparing a phosphorus-doped cobalt aluminum / carbon-based composite material:

[0076] Step 1: Preparation of modified cobalt aluminum double hydroxide

[0077] Cobalt chloride hexahydrate, aluminum chloride hexahydrate and urea were added into deionized water according to the proportion, and ultrasonic treatment was performed for 9 minutes to obtain a first precursor solution having a concentration of 0.01 mol / L of cobalt chloride hexahydrate, 0.09 mol / L of aluminum chloride hexahydrate and 0.035 mol / L of urea;

[0078] The first precursor solution was subjected to a hydrothermal reaction at 100° C. for 24 hours, and the hydrothermal reaction product was centrifugally washed twice with anhydrous ethanol and deionized water respectively, the centrifugal speed was 5000 r / min, and the time of each centrifugal washing was 1 minute, and the product after centrifugal washing was dried at 60° C. for 24 hours to obtain cobalt aluminum double hydroxide;

[0079] Dissolving cobalt aluminum double hydroxide in anhydrous ethanol according to a ratio and adding polyvinyl pyrrolidone to prepare a modified solution with a concentration of 3.3 g / L of cobalt aluminum double hydroxide and a concentration of 0.03 mol / L of polyvinyl pyrrolidone;

[0080] The prepared modified solution was stirred at room temperature at a stirring speed of 500 r / min for 12 h, and the stirred product was centrifugally washed three times with anhydrous ethanol and deionized water respectively, the centrifugal speed was 5000 r / min, and the time of each centrifugal washing was 1 min. The product after centrifugal washing was dried at 60° C. for 24 h to obtain modified cobalt aluminum double hydroxide;

[0081] Step 2: Preparation of sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite

[0082] Sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water, gelatin, formaldehyde and tannic acid are prepared according to the ratio. Specifically, 0.8 mg of sodium hypophosphite, 4 mg of modified cobalt aluminum double hydroxide material, 0.09 g of gelatin, 2 μL of formaldehyde and 0.002 mg of tannic acid are prepared for every 1 ml of deionized water;

[0083] Sodium hypophosphite and modified cobalt aluminum double hydroxide were dissolved in deionized water according to the ratio, and gelatin was added after ultrasonic treatment for 9 minutes and allowed to stand at room temperature for 40 minutes to obtain a second precursor solution, and the second precursor solution was reacted in a first water bath at a temperature of 50° C. for 30 minutes to obtain a third precursor solution;

[0084] Adding formaldehyde and tannic acid to a third precursor solution according to a ratio to prepare a fourth precursor solution, performing a second water bath reaction on the prepared fourth precursor solution, and freezing and drying the product of the second water bath reaction, including: performing a second water bath reaction on the fourth precursor solution at 50° C. for 20 minutes, freeze-drying the product of the second water bath reaction at -80° C. for 36 hours, and preparing a sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite;

[0085] Step 3: Preparation of phosphorus-doped cobalt aluminum / carbon-based composite materials

[0086] The sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite was placed in a nitrogen atmosphere, heated to 800°C at a heating rate of 2°C / min, kept at this temperature for 2h, cooled to 500°C at a rate of 5°C / min, and then naturally cooled to room temperature to obtain a phosphorus-doped cobalt aluminum / carbon-based composite material.

[0087] Example 4

[0088] A method for preparing a phosphorus-doped cobalt aluminum / carbon-based composite material:

[0089] Step 1: Preparation of modified cobalt aluminum double hydroxide

[0090] Cobalt chloride hexahydrate, aluminum chloride hexahydrate and urea are added to deionized water according to a ratio, and ultrasonic treatment is performed for 10 minutes to obtain a first precursor solution having a concentration of 0.01 mol / L of cobalt chloride hexahydrate, 0.09 mol / L of aluminum chloride hexahydrate and 0.035 mol / L of urea;

[0091] The first precursor solution was subjected to a hydrothermal reaction at 100° C. for 24 hours, and the hydrothermal reaction product was centrifugally washed twice with anhydrous ethanol and deionized water respectively, the centrifugal speed was 5000 r / min, and the time of each centrifugal washing was 1 minute, and the product after centrifugal washing was dried at 60° C. for 24 hours to obtain cobalt aluminum double hydroxide;

[0092] Dissolving cobalt aluminum double hydroxide in anhydrous ethanol according to a ratio and adding polyvinyl pyrrolidone to prepare a modified solution with a concentration of 3.3 g / L of cobalt aluminum double hydroxide and a concentration of 0.03 mol / L of polyvinyl pyrrolidone;

[0093] The prepared modified solution was stirred at room temperature at a stirring speed of 500 r / min for 15 h, and the stirred product was centrifugally washed three times with anhydrous ethanol and deionized water respectively, the centrifugal speed was 5000 r / min, and the time of each centrifugal washing was 1 min. The product after centrifugal washing was dried at 60° C. for 24 h to obtain modified cobalt aluminum double hydroxide;

[0094] Step 2: Preparation of sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite

[0095] Sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water, gelatin, formaldehyde and tannic acid are prepared according to the ratio. Specifically, 0.4 mg of sodium hypophosphite, 4 mg of modified cobalt aluminum double hydroxide material, 0.1 g of gelatin, 2 μL of formaldehyde and 0.002 mg of tannic acid are prepared for every 1 ml of deionized water;

[0096] Sodium hypophosphite and modified cobalt aluminum double hydroxide are dissolved in deionized water according to a ratio, and gelatin is added after ultrasonic treatment for 10 minutes and allowed to stand at room temperature for 30 minutes to obtain a second precursor solution, and the second precursor solution is reacted in a first water bath at a temperature of 50° C. for 30 minutes to obtain a third precursor solution;

[0097] Adding formaldehyde and tannic acid to a third precursor solution according to a ratio to prepare a fourth precursor solution, performing a second water bath reaction on the prepared fourth precursor solution, and freezing and drying the product of the second water bath reaction, including: performing a second water bath reaction on the fourth precursor solution at 50° C. for 20 minutes, freeze-drying the product of the second water bath reaction at -80° C. for 36 hours, and preparing a sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite;

[0098] Step 3: Preparation of phosphorus-doped cobalt aluminum / carbon-based composite materials

[0099] The sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite was placed in a nitrogen atmosphere, heated to 700°C at a heating rate of 2°C / min, kept at this temperature for 2h, cooled to 500°C at a rate of 5°C / min, and then naturally cooled to room temperature to obtain a phosphorus-doped cobalt aluminum / carbon-based composite material.

[0100] Example 5

[0101] A method for preparing a phosphorus-doped cobalt aluminum / carbon-based composite material:

[0102] Step 1: Preparation of modified cobalt aluminum double hydroxide

[0103] Cobalt chloride hexahydrate, aluminum chloride hexahydrate and urea are added to deionized water according to a ratio, and ultrasonic treatment is performed for 10 minutes to obtain a first precursor solution having a concentration of 0.01 mol / L of cobalt chloride hexahydrate, 0.09 mol / L of aluminum chloride hexahydrate and 0.035 mol / L of urea;

[0104] The first precursor solution was subjected to a hydrothermal reaction at 100° C. for 24 hours, and the hydrothermal reaction product was centrifugally washed twice with anhydrous ethanol and deionized water respectively, the centrifugal speed was 5000 r / min, and the time of each centrifugal washing was 1 minute, and the product after centrifugal washing was dried at 60° C. for 24 hours to obtain cobalt aluminum double hydroxide;

[0105] Dissolving cobalt aluminum double hydroxide in anhydrous ethanol according to a ratio and adding polyvinyl pyrrolidone to prepare a modified solution with a concentration of 3.3 g / L of cobalt aluminum double hydroxide and a concentration of 0.03 mol / L of polyvinyl pyrrolidone;

[0106] The prepared modified solution was stirred at room temperature at a stirring speed of 500 r / min for 12 h, and the stirred product was centrifugally washed three times with anhydrous ethanol and deionized water respectively, the centrifugal speed was 5000 r / min, and the time of each centrifugal washing was 1 min. The product after centrifugal washing was dried at 60° C. for 24 h to obtain modified cobalt aluminum double hydroxide;

[0107] Step 2: Preparation of sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite

[0108] Sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water, gelatin, formaldehyde and tannic acid are prepared according to the ratio. Specifically, 0.4 mg of sodium hypophosphite, 4 mg of modified cobalt aluminum double hydroxide material, 0.08 g of gelatin, 2 μL of formaldehyde and 0.002 mg of tannic acid are prepared for every 1 ml of deionized water;

[0109] Sodium hypophosphite and modified cobalt aluminum double hydroxide were dissolved in deionized water according to the ratio, and gelatin was added after ultrasonic treatment for 7 minutes and allowed to stand at room temperature for 30 minutes to obtain a second precursor solution, and the second precursor solution was reacted in a first water bath at 50° C. for 30 minutes to obtain a third precursor solution;

[0110] Adding formaldehyde and tannic acid to a third precursor solution according to a ratio to prepare a fourth precursor solution, performing a second water bath reaction on the prepared fourth precursor solution, and freezing and drying the product of the second water bath reaction, including: performing a second water bath reaction on the fourth precursor solution at 50° C. for 20 minutes, and freeze-drying the product of the second water bath reaction at -80° C. for 36 hours to obtain a sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite;

[0111] Step 3: Preparation of phosphorus-doped cobalt aluminum / carbon-based composite materials

[0112] The sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite was placed in a nitrogen atmosphere, heated to 700°C at a heating rate of 2°C / min, kept at this temperature for 2h, cooled to 500°C at a rate of 5°C / min, and then naturally cooled to room temperature to obtain a phosphorus-doped cobalt aluminum / carbon-based composite material.

[0113] Example 6

[0114] A method for preparing a phosphorus-doped cobalt aluminum / carbon-based composite material:

[0115] Step 1: Preparation of modified cobalt aluminum double hydroxide

[0116] Cobalt chloride hexahydrate, aluminum chloride hexahydrate and urea are added to deionized water according to a ratio, and ultrasonic treatment is performed for 10 minutes to obtain a first precursor solution having a concentration of 0.01 mol / L of cobalt chloride hexahydrate, 0.09 mol / L of aluminum chloride hexahydrate and 0.035 mol / L of urea;

[0117] The first precursor solution was subjected to a hydrothermal reaction at 100° C. for 24 hours, and the hydrothermal reaction product was centrifugally washed twice with anhydrous ethanol and deionized water respectively, the centrifugal speed was 5000 r / min, and the time of each centrifugal washing was 1 minute, and the product after centrifugal washing was dried at 60° C. for 24 hours to obtain cobalt aluminum double hydroxide;

[0118] Dissolving cobalt aluminum double hydroxide in anhydrous ethanol according to a ratio and adding polyvinyl pyrrolidone to prepare a modified solution with a concentration of 3.3 g / L of cobalt aluminum double hydroxide and a concentration of 0.03 mol / L of polyvinyl pyrrolidone;

[0119] The prepared modified solution was stirred at room temperature at a stirring speed of 500 r / min for 12 h, and the stirred product was centrifugally washed three times with anhydrous ethanol and deionized water respectively, the centrifugal speed was 5000 r / min, and the time of each centrifugal washing was 1 min. The product after centrifugal washing was dried at 60° C. for 24 h to obtain modified cobalt aluminum double hydroxide;

[0120] Step 2: Preparation of sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite

[0121] Sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water, gelatin, formaldehyde and tannic acid are prepared according to the ratio. Specifically, 0.4 mg of sodium hypophosphite, 4 mg of modified cobalt aluminum double hydroxide material, 0.06 g of gelatin, 2 μL of formaldehyde and 0.002 mg of tannic acid are prepared for every 1 ml of deionized water;

[0122] Sodium hypophosphite and modified cobalt aluminum double hydroxide were dissolved in deionized water according to the ratio, and gelatin was added after ultrasonic treatment for 7 minutes and allowed to stand at room temperature for 30 minutes to obtain a second precursor solution, and the second precursor solution was reacted in a first water bath at 50° C. for 30 minutes to obtain a third precursor solution;

[0123] Adding formaldehyde and tannic acid to a third precursor solution according to a ratio to prepare a fourth precursor solution, performing a second water bath reaction on the prepared fourth precursor solution, and freezing and drying the product of the second water bath reaction, including: performing a second water bath reaction on the fourth precursor solution at 50° C. for 20 minutes, and freeze-drying the product of the second water bath reaction at -80° C. for 36 hours to obtain a sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite;

[0124] Step 3: Preparation of phosphorus-doped cobalt aluminum / carbon-based composite materials

[0125] The sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite was placed in a nitrogen atmosphere, heated to 700°C at a heating rate of 2°C / min, kept at this temperature for 2h, cooled to 500°C at a rate of 5°C / min, and then naturally cooled to room temperature to obtain a phosphorus-doped cobalt aluminum / carbon-based composite material.

[0126] Example 7

[0127] The graphitization degree of the phosphorus-doped cobalt aluminum / carbon-based composite materials prepared in Example 1, Example 2, Example 3, Example 4, Example 5 and Example 6 was tested by a laser Raman spectrometer of model Invia Qontor, with an excitation wavelength of 532 nm and a spectral range of 500-2300 cm -1 The laser Raman spectra of the phosphorus-doped cobalt aluminum / carbon-based composite materials prepared in Example 1, Example 2, Example 3, Example 4, Example 5 and Example 6 are shown in Table 1. Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 and Figure 6 In the laser Raman spectrum, at 1341cm -1 The D peak at 1586 cm -1 The intensity ratio of the G peak at D / I G ) represents the degree of graphitization of the material. The larger the ratio, the lower the degree of graphitization of the material.

[0128] Figure 1 This is the laser Raman spectrum of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 1 of the present invention. Figure 2 This is the laser Raman spectrum of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 2 of the present invention. Figure 3 This is the laser Raman spectrum of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 3 of the present invention, such as Figure 1 , Figure 2 and Figure 3 As shown, the phosphorus-doped cobalt aluminum / carbon-based composite materials prepared in Example 1, Example 2 and Example 3 have a D / I G The values ​​are 1.01, 1.04 and 1.05, respectively. With the increase of carbonization temperature, the graphitization degree of phosphorus-doped cobalt aluminum / carbon-based composites decreases. It can be seen that low temperature is beneficial to increase the graphitization degree of carbon. This is because during low-temperature carbonization, the decomposition and phase change of cobalt aluminum double hydroxide are incomplete, and the interaction between metal ions and carbon precursors helps to form a partially ordered graphite structure. The corresponding carbon ordering increases, and the conductivity and electron transmission ability of the material are enhanced.

[0129] Figure 4 This is the laser Raman spectrum of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 4 of the present invention. Figure 5 This is the laser Raman spectrum of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 5 of the present invention. Figure 6 The laser Raman spectrum of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 6 of the present invention is as follows: Figure 4 , Figure 5 and Figure 6 As shown, the phosphorus-doped cobalt aluminum / carbon-based composite materials prepared in Example 4, Example 5 and Example 6 have a D / I GThe values ​​are 1.04, 1.03 and 1.09 respectively. When the carbonization temperature is the same, the degree of graphitization of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in the embodiment of the present invention mainly depends on the proportion of the phosphorus doping amount. The mild water bath process ensures that the phosphorus source will not decompose. Phosphorus will form stable phosphorus-carbon compounds with carbon at high temperatures, which can regulate the degree of graphitization by affecting the orderly arrangement of carbon atoms. The comprehensive control of the pyrolysis temperature and the phosphorus doping amount to finely regulate the degree of graphitization is more conducive to the synergistic improvement of the absorption and thermal conductivity properties.

[0130] The morphology of the sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite, the morphology of the phosphorus-doped cobalt aluminum / carbon-based composite material, and the element distribution of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 5 were characterized by a cold field emission scanning electron microscope of model Hitachi Regulus8230, and the acceleration voltage used was 2 kV. Figure 7 This is a scanning electron microscope image of the sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite prepared in Example 5 of the present invention; Figure 8 This is a scanning electron microscope image of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 5 of the present invention; Fig. 9 This is the element distribution diagram of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 5 of the present invention.

[0131] like Figure 7 As shown, the sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite prepared in Example 5 has a porous structure. The porous structure can reduce the density of the material, and the interface effect and internal scattering in the void structure are conducive to the dissipation of electromagnetic wave energy; Figure 8 As shown, the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 5 still retains a porous structure, the surface of the material becomes rough, and the flaky cobalt aluminum double hydroxide is transformed into granular metal particles distributed on the surface of the material. The cobalt aluminum double hydroxide receives high-temperature energy and is transformed into metal particles with better crystallinity. The system energy is small and the structure is more stable. Fig. 9 As shown, the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 5 is distributed with cobalt, aluminum, phosphorus, carbon and oxygen elements, the carbon content is relatively high, the cobalt and aluminum content is relatively low, and the phosphorus element is evenly distributed in the carbon matrix. Phosphorus doping can change the lattice structure and electronic structure of the material and improve the mobility of carriers. The phosphorus-carbon bonds and phosphorus-oxygen bonds formed after phosphorus doping are conducive to the transfer and diffusion of heat.

[0132] The ROHDE & SCHWARZ vector network analyzer was used to test the electromagnetic parameters of the phosphorus-doped cobalt aluminum / carbon-based composite materials prepared in Example 2 and Example 5 in the frequency range of 2-18 GHz using the coaxial cable method, and the reflection loss curve was calculated. Fig.10 and Fig.11 .

[0133] Fig.10 The reflection loss curve of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 2 of the present invention is shown in FIG. Specifically, the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 2 is mixed with polyvinylidene fluoride at a filling ratio of 25% and then pressed into a hollow ring. The electromagnetic parameter test is performed and the reflection loss curve is obtained at a thickness of 4 mm. Fig.10 It can be seen that the optimal reflection loss of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 2 is -38.8 dB, and the effective absorption bandwidth (RL≤-10dB) is 2.1 GHz. The rich pore structure provides more paths to increase the propagation and attenuation of electromagnetic waves. At the same time, the high specific surface area can obtain more active sites, which can effectively capture electromagnetic waves. Therefore, the phosphorus-doped cobalt aluminum / carbon-based composite material has high-efficiency wave absorbing performance.

[0134] Fig.11 The reflection loss curve of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 5 of the present invention is shown in FIG. Specifically, the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 5 is mixed with polyvinylidene fluoride at a filling ratio of 25% and then pressed into a hollow ring. The electromagnetic parameter test is performed and the reflection loss curve is obtained at a thickness of 2.4 mm. Fig.11 It can be seen that the optimal reflection loss of the phosphorus-doped cobalt aluminum / carbon-based composite material prepared in Example 5 is -59 dB, the effective absorption bandwidth is 4.6 GHz, the absorption intensity and the effective bandwidth are significantly increased, the three-dimensional interconnected conductive network constructed by carbon with a higher degree of graphitization, and the increase in the electron concentration of the system brought about by phosphorus doping, jointly enhance the material's electrical conductivity loss, and together with the magnetic loss provided by the magnetic metal cobalt component, promote the absorption of electromagnetic waves by the phosphorus-doped cobalt aluminum / carbon-based composite material.

[0135] The thermal conductivity of the phosphorus-doped cobalt aluminum / carbon-based composite materials prepared in Example 1 and Example 5 was tested by laser flash method using a laser thermal conductivity meter of model NETZSCH LFA457. The thermal conductivity of the materials prepared in Example 1 and Example 5 is shown in Table 1 respectively.

[0136] Table 1

[0137]

[0138]

[0139] As shown in Table 1, the thermal conductivity of the phosphorus-doped cobalt aluminum / carbon-based composite materials prepared in Example 1 and Example 5 is 254% and 260% higher than that of polyvinylidene fluoride, respectively. The porous structure can effectively disperse heat, and the heat transfer between the pores is carried out through the skeleton. High-temperature carbonization and phosphorus doping make the material highly graphitized. The three-dimensional pathways formed by the interconnected graphitized carbon can increase the transmission free path of phonons. In addition, phosphorus doping provides additional electrons, improves the mobility of electrons, and makes the thermal conductivity reach 0.719 W / (m·K) and 0.731 W / (m·K).

[0140] A method for preparing a phosphorus-doped cobalt-aluminum carbon-based composite material, a material and an application thereof according to an embodiment of the present invention have the following beneficial technical effects:

[0141] 1. Through hydrothermal and modification treatment, modified cobalt aluminum double hydroxide with regular morphology, uniform size and better dispersibility is prepared. The surface of modified cobalt aluminum double hydroxide is rich in polar groups and can form a good interface with aerogel. The magnetic component cobalt can provide strong magnetic loss, and the aluminum component plays a dual role. On the one hand, it can adjust the impedance matching and improve the wave absorption characteristics of the structure. On the other hand, it can increase the transmission free path of phonons and improve thermal conductivity. The synergistic effect of thermal conductivity and wave absorption of phosphorus-doped cobalt aluminum / carbon-based materials is significantly enhanced;

[0142] 2. During the water bath and freeze-drying preparation process, the controlled addition of formaldehyde and tannic acid promoted the cross-linking of gelatin molecular chains, thereby obtaining a highly stable sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel high porosity composite. The aerogel has a rich pore structure and a large specific surface area. While reducing the density, it can also make electromagnetic waves reflect and absorb multiple times;

[0143] 3. Phosphorus-doped cobalt aluminum / carbon-based composites were prepared by phosphorus doping in a high-temperature inert atmosphere, which significantly increased the electron concentration of the system and achieved efficient electron transmission in the three-dimensional interconnected structure of the material, thereby enhancing the ability of electron heat transfer and electrical conductivity loss, while also improving the crystallinity of the material and the degree of graphitization of carbon;

[0144] 4. The phosphorus-doped cobalt aluminum / carbon-based composite material prepared by the present invention has a reflection loss performance of -59dB, an effective wave absorption bandwidth of 4.6GHz, and a thermal conductivity of 0.731W / (m·K). It has a small filling amount, a large wave absorption intensity, and a high thermal conductivity, showing excellent thermal conductive wave absorption performance, which is conducive to the preparation of a new type of "thin, light, wide, and strong" thermal conductive wave absorbing material;

[0145] 5. The raw materials of the method of the present invention are green and environmentally friendly, the cost is controllable, the repeatability is good, the preparation cycle is short and the energy consumption is low, no special equipment is required, and it is suitable for large-scale production and application. The prepared phosphorus-doped cobalt aluminum / carbon-based composite thermal conductive and absorbing material is more competitive in multifunctional integrated application scenarios such as electronic packaging, medical equipment, antenna materials, and 5G base stations.

[0146] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing a phosphorus-doped cobalt aluminum / carbon-based composite material, characterized in that: The method comprises the following steps: Step 1: Preparation of modified cobalt aluminum double hydroxide A first precursor solution is prepared by using cobalt chloride hexahydrate, aluminum chloride hexahydrate, urea and deionized water according to a ratio, the prepared first precursor solution is subjected to a hydrothermal reaction, and the hydrothermal reaction product is washed and dried to obtain cobalt aluminum double hydroxide; The prepared cobalt aluminum double hydroxide is modified by using ethanol and polyvinyl pyrrolidone according to a ratio, and the modified product is washed and dried to obtain modified cobalt aluminum double hydroxide; Step 2: Preparation of sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite Sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water, gelatin, formaldehyde and tannic acid are prepared according to the proportion; Sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water and gelatin are mixed according to a ratio to prepare a second precursor solution, and the prepared second precursor solution is subjected to a first water bath reaction to obtain a third precursor solution; Adding formaldehyde and tannic acid to the third precursor solution according to a ratio to prepare a fourth precursor solution, subjecting the prepared fourth precursor solution to a second water bath reaction, and freezing and drying the second water bath reaction product to obtain a sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite; Step 3: Preparation of phosphorus-doped cobalt aluminum / carbon-based composite materials The sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite is carbonized in a nitrogen atmosphere to prepare a phosphorus-doped cobalt aluminum / carbon-based composite material; In step one, a hydrothermal reaction is performed on the prepared first precursor solution, and the hydrothermal reaction product is washed and dried, including: performing a hydrothermal reaction on the first precursor solution at a temperature of 100° C. for 24 hours.

2. The method for preparing the phosphorus-doped cobalt aluminum / carbon-based composite material according to claim 1, characterized in that: In step 1, a first precursor solution is prepared by using cobalt chloride hexahydrate, aluminum chloride hexahydrate, urea and deionized water according to a ratio, including: adding cobalt chloride hexahydrate, aluminum chloride hexahydrate and urea to deionized water according to a ratio, and ultrasonically treating for 5-10 minutes to obtain a first precursor solution with a concentration of 0.01 mol / L of cobalt chloride hexahydrate, 0.09 mol / L of aluminum chloride hexahydrate, and 0.035 mol / L of urea.

3. The method for preparing the phosphorus-doped cobalt aluminum / carbon-based composite material according to claim 1, characterized in that: In step one, a hydrothermal reaction is carried out on the prepared first precursor solution, and the hydrothermal reaction product is washed and dried. The step also includes: centrifugally washing the hydrothermal reaction product 2-3 times with anhydrous ethanol and deionized water respectively, with a centrifugal speed of 5000 r / min, and each centrifugal washing time is 1 minute, and the product after centrifugal washing is dried at 60°C for 24 hours.

4. The method for preparing the phosphorus-doped cobalt aluminum / carbon-based composite material according to claim 1, characterized in that: In step 1, the prepared cobalt aluminum double hydroxide is modified by using ethanol and polyvinyl pyrrolidone according to a ratio, and the modified product is washed and dried, comprising: Dissolving cobalt aluminum double hydroxide in anhydrous ethanol according to a ratio and adding polyvinyl pyrrolidone to prepare a modified solution with a concentration of 3.3 g / L of cobalt aluminum double hydroxide and a concentration of 0.03 mol / L of polyvinyl pyrrolidone; The prepared modified solution was stirred at room temperature at a stirring speed of 300-500 r / min for 8-15 h, and the stirred product was centrifugally washed 2-3 times with anhydrous ethanol and deionized water respectively, the centrifugal speed was 5000 r / min, and the time of each centrifugal washing was 1 min. The product after centrifugal washing was dried at 60°C for 12-24 h.

5. The method for preparing the phosphorus-doped cobalt aluminum / carbon-based composite material according to claim 1, characterized in that: In step 2, sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water, gelatin, formaldehyde and tannic acid are prepared according to the ratio, including: 0.2-0.8 mg of sodium hypophosphite, 4 mg of modified cobalt aluminum double hydroxide material, 0.06-0.1 g of gelatin, 2 μL of formaldehyde and 0.002 mg of tannic acid per 1 ml of deionized water.

6. The method for preparing the phosphorus-doped cobalt aluminum / carbon-based composite material according to claim 1, characterized in that: In step two, sodium hypophosphite, modified cobalt aluminum double hydroxide, deionized water and gelatin are prepared into a second precursor solution according to a ratio, and the prepared second precursor solution is subjected to a first water bath reaction to obtain a third precursor solution, including: sodium hypophosphite and modified cobalt aluminum double hydroxide are dissolved in deionized water according to a ratio, and gelatin is added after ultrasonic treatment for 5-10 minutes and allowed to stand at room temperature for 30-50 minutes to obtain a second precursor solution, and the second precursor solution is subjected to a first water bath reaction at a temperature of 50°C for 30 minutes to obtain a third precursor solution.

7. The method for preparing the phosphorus-doped cobalt aluminum / carbon-based composite material according to claim 1, characterized in that: In step two, the prepared fourth precursor solution is subjected to a second water bath reaction, and the product of the second water bath reaction is frozen and dried, including: a second water bath reaction of the fourth precursor solution at 50°C for 20 minutes, and freeze-drying the product of the second water bath reaction at -80°C for 24-48 hours.

8. The method for preparing the phosphorus-doped cobalt aluminum / carbon-based composite material according to claim 1, characterized in that: In step three, the sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite is carbonized in a nitrogen atmosphere, including: placing the sodium hypophosphite / modified cobalt aluminum double hydroxide / aerogel composite in a nitrogen atmosphere, heating the mixture to 600-800°C at a heating rate of 2°C / min, keeping the temperature for 2h, cooling the mixture to 500°C at a rate of 5°C / min, and then naturally cooling the mixture to room temperature.

9. A phosphorus-doped cobalt aluminum / carbon-based composite material, characterized in that: The phosphorus-doped cobalt aluminum / carbon-based composite material is prepared according to any one of the methods described in claims 1-8.

10. An application of a phosphorus-doped cobalt aluminum / carbon-based composite material, characterized in that: Use of the phosphorus-doped cobalt aluminum / carbon-based composite material as claimed in claim 9 as a thermal conductive and wave absorbing material.

Citation Information

Patent Citations

  • Three-dimensional high-thermal-conductivity attapulgite / graphene oxide aerogel composite phase change material and preparation method thereof

    CN115612461A

  • Preparation method of structure-enhanced magnetic graphene aerogel wave-absorbing material

    CN117263172A

  • Preparation method for biomass aerogel antibacterial material

    CN107624786A

  • Preparation method and application of formed layered double hydroxides and derivatives thereof

    CN113600142A